Rare adrenal cavernous hemangioma: a case report highlighting diagnostic challenges - Antar, Ryan Michael; Farag, Christian Mark; Youssef, Kirolos; Xu, Vincent; Drouaud, Arthur; Panitch, Noah; Tariq, Zoon; Alzeer, Ali; Whalen, Michael J. (Frontiers in Surgery, 2023)
Introduction: Adrenal cavernous hemangiomas are rare benign vascular tumors that pose significant diagnostic challenges. Despite their benign nature, features overlapping with malignancies often complicate management decisions. Case Presentation: A 64-year-old male presented with a 4.4 cm necrotic left adrenal mass discovered incidentally on imaging. His medical history included papillary thyroid carcinoma, with subsequent thyroidectomy and radioactive iodine ablation. Evaluations for hiccups revealed multiple lung nodules, hypertrophic cardiomyopathy, and anemia. Given the patient’s previous cancer history, elevated aldosterone/renin ratio, and mass size, our multidisciplinary tumor board decided to proceed with a left adrenalectomy. Post-surgical pathology confirmed a diagnosis of adrenal cavernous hemangioma. Conclusion: The occurrence of ambiguous adrenal mass with other pathologies, such as our patient’s papillary thyroid carcinoma, complicates the diagnostic and therapeutic landscape. As demonstrated in our case, opting for surgery remains a viable solution for adrenal cavernous hemangiomas, especially for masses greater than 4 cm. Interdisciplinary collaboration, exemplified by our tumor board's decision-making process, is crucial for optimal management. This case underscores the need for a multifaceted approach when confronting adrenal masses with such diagnostic ambiguity.